`Just do a little more`: examining expertise in high performance sport from a sociocultural learning perspective - Barker, D.; Barker-Ruchti, N.; Rynne, S.; Lee, J. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
Research suggests that extensive training is necessary for the development of sporting expertise. Research also suggests that extensive training can lead to overuse injuries. The aims of this paper are to: (1) expand the concept of expertise in high performance sport, and (2) contribute to the discussion of how high performance athletes move towards expert performance in sustainable ways. To achieve these aims, data from retrospective interviews with four Olympians from four different sports are presented. As a way of extending traditional approaches, a pedagogical framework focusing on dispositional learning is employed to examine athletic development. The notion of threshold concepts is used as a specific analytic tool for thinking about how athletes come to make sense of their sporting environments. Interpretations of the data provide insights into the nature of thresholds in high performance sport, factors that facilitate threshold crossing, and factors that may prevent athletes from making advances, all of which have implications for practitioners interested in developing expertise. Fulltext request: https://www.researchgate.net/publication/263598745_Just_do_a_little_more_examining_expertise_in_high_performance_sport_from_a_sociocultural_learning_perspective